Analysis Of Coffee Production In Indonesia - Elvin Desi Martauli (JASc (Journal of Agribusiness Sciences), 2018)
Indonesia is one of the largest coffee producing and exporting countries in the world, where coffee crops also contribute to the Indonesian economy. In general there are two types of coffee grown on Indonesian coffee plantations namely Robusta and Arabica Coffee. Robusta coffee is a coffee that has a higher production when compared with arabica coffee. Until now, the total area, production and productivity of coffee plantations in Indonesia, both from Robusta coffee and arabica coffee are still dominated by public plantation (PR) with 95.37% of coffee area. The area of coffee production in Indonesia is estimated to be about 1.3 million hectares, spread across North Sumatra, Java, and Sulawesi. Robusta coffee is commonly planted by farmers in South Sumatra, Lampung and East Java, whereas arabica coffee is commonly planted by farmers in Aceh, North Sumatra, South Sulawesi, Bali and Flores.